2019
DOI: 10.1055/s-0039-1692628
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Skin Closure Device for Total Knee Arthroplasty: Randomized Controlled Trial versus Staples

Abstract: Twenty-five patients undergoing simultaneous, bilateral total knee arthroplasty (TKA) were randomized to receive skin closure with Zip device on one knee and staples on the other. Patients' pain and scar appearance were rated from 0 (best) to 10 (worst). Knee arc of motion was measured by a physical therapist. At 2 weeks postoperatively, pain scores were significantly better with the Zip device during device wear (p = 0.03) and during device removal (p = 0.003); arc of motion was significantly better with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…The zipper device provides precise, adjustable, and tension‐free adaptation of the incision edges for a sufficient time and minimal trauma to the skin and underlying tissues, without resulting in an ischemic condition that could impact healing and scarring, thus make it beneficial to a good cosmetic result 16,26 . Several studies reported similar results that a better cosmesis was observed in the zipper group compared with stapler group 6,8,26 . Furthermore, a distinctive feature of the zipper was that no need of removing sutures and bandages thus cause less painful, which further improved the patient satisfactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The zipper device provides precise, adjustable, and tension‐free adaptation of the incision edges for a sufficient time and minimal trauma to the skin and underlying tissues, without resulting in an ischemic condition that could impact healing and scarring, thus make it beneficial to a good cosmetic result 16,26 . Several studies reported similar results that a better cosmesis was observed in the zipper group compared with stapler group 6,8,26 . Furthermore, a distinctive feature of the zipper was that no need of removing sutures and bandages thus cause less painful, which further improved the patient satisfactions.…”
Section: Discussionmentioning
confidence: 99%
“…16,26 Several studies reported similar results that a better cosmesis was observed in the zipper group compared with stapler group. 6,8,26 Furthermore, a distinctive feature of the zipper was that no need of removing sutures and bandages thus cause less painful, which further improved the patient satisfactions.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…[ 3 , 4 ] In addition to running subcuticular or intermittent closure using staples or barbed sutures, [ 5 7 ] a novel “zip” device and skin adhesives have also been explored for post-TKA skin closure. [ 8 , 9 ] Although intermittent closure with silk suture is routinely used for different surgical wounds, subcuticular closure with absorbable sutures are increasingly being considered owing to their convenience and better cosmetic appearance. In this retrospective study, we compared the 6-month clinical outcome of running subcuticular closure and intermittent closure post-TKA.…”
Section: Introductionmentioning
confidence: 99%